1993
DOI: 10.1111/j.1432-1033.1993.tb18096.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigments induce folding of light‐harvesting chlorophyll a/b‐binding protein

Abstract: The conformational behaviour of the light-harvesting chlorophyll &-binding protein (LHCP), the apoprotein of the major light-harvesting complex (LHCII) of photosystem I1 in plants, has been studied. According to the circular dichroism in the ultraviolet range measured with isolated LHCII, the protein in the complex adopts a folded structure with a high content of a helix (about 60%), whereas the non-pigmented, solubilized protein has a less ordered structure (about 20% a helix).LHCP-pigment complexes that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
131
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 32 publications
3
131
0
3
Order By: Relevance
“…Pigments may also play a more active role during the insertion process. Pigment binding initiates the refolding of detergent-denatured LHCP in vitro (12). This observation suggests that pigment-triggered renaturation of LHCP may play a similar role when the protein is inserted into the thylakoid, the binding of pigments and the concomitant refolding of LHCP being the driving force for translocating parts of the protein across the membrane (13).…”
mentioning
confidence: 83%
“…Pigments may also play a more active role during the insertion process. Pigment binding initiates the refolding of detergent-denatured LHCP in vitro (12). This observation suggests that pigment-triggered renaturation of LHCP may play a similar role when the protein is inserted into the thylakoid, the binding of pigments and the concomitant refolding of LHCP being the driving force for translocating parts of the protein across the membrane (13).…”
mentioning
confidence: 83%
“…The distance between these two labels (106/160) is probably defined by the formation (or completion) of helix H3. Earlier CD measurements had revealed that ␣-helix formation in LHCII apoprotein (beyond the helical structure preformed in dodecyl sulfate solution) is dependent on pigment binding (27), and that most but not all of it happens during the faster reaction phase in the range of 10 s to 1 min. The helix formation positioning labels 106/160 is not likely to be triggered by Chls binding locally to this helical domain, since these are all Chl b binding sites whose occupation takes place during the slower kinetic phase of several minutes.…”
Section: Lhcii Protein Folds In Two Apparent Phases In the Range Of Lmentioning
confidence: 99%
“…(15). For steady-state DEER the spin-labeled complexes were reconstituted using the detergent-exchange procedure (henceforward called ''standard reconstitution'') as described in (27) except that 10 mM ␤-mercaptoethanol (␤-ME) was used as a reductant. Purification of LHCII and preparation of EPR samples were performed as described in (11).…”
Section: Lhcii Protein Folds In Two Apparent Phases In the Range Of Lmentioning
confidence: 99%
“…WT and mutant apoproteins were isolated from the SG13009 strain of Escherichia coli transformed with constructs following a protocol described previously (17,(21)(22)(23). Reconstitution and purification of protein-pigment complexes were performed as described (11,12).…”
Section: Dna Constructions and Isolation Of Overexpressed Lhcamentioning
confidence: 99%